Implementação de Trabalho de Conclusão de Curso em cadeia criativa em uma escola da rede pública do estado de São Paulo - Santos, Josafá Miranda dos (2018)
This research aims to critically analyze how the Creative Chain and Critical-Collaborative Research could contribute to the implementation of the development of the Final Paper processes (trabalho de conclusão de curso, TCC, acronym in Portuguese) in the 3rd years of secondary education using their theoretical and methodological concepts. and, at the same time, collaborate with the development of managers, teachers and students as researchers in the 3rd years of secondary education. The research was based on the following question: 'How to implement the practice of the Final Paper processes in the 3rd years of High School through Creative Chain?” involving critically and creatively researchers from three instances - management team, teachers and students? This study is based on the principles of Socio- Historical-Cultural Activity Theory, focusing on the understanding of the historical, social and cultural development process of the teachers and students involved in this research. In order to answer the question, a Critical-Collaborative research was carried out, with the participation of -administrators, coordinators, teachers from different areas of knowledge, researchers from PUC-SP, and students from a school located in the city of Guarulhos, São Paulo. Data collection was carried out by audio and video recordings from several activities (meetings with researchers, management team and teachers, and meetings among teachers, coordinators and students), as well as summaries for the assignments developed by students. The analysis, through actions of critical reflection (Describe, Inform, Confront and Reconstruct), allowed both to conduct data discussion and to enable the development of this project. Results show that the group achieved collaborative work when it comes to the development of the participants as researchers as well as the proposals to implement the Final Paper processes, since the participants interacted, exchanged experiences, researched and performed critical analysis of reality. This study made it possible to create circumstances for the implementation and organization of the Final Paper as a permanent activity of the school unit, collaborating with teacher development process and pedagogical action